METHOD TO MAXIMISE THE HEAT TRANSFER THROUGH FINS - sehgal, Karan; pratap, Anuj; kuhar, Ravi (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
This study presents the results of computational numerical analysis of air flow and heat transfer in a light weight automobile engine, considering three different morphology pin fins. A numerical study was conducted to find the optimum pin shape based on minimum pressure drop and maximizing the heat transfer across the Automobile engine body. The results indicate that the drop shaped pin fins show improved results on the basis of heat transfer and pressure drop by comparing other fins. The reason behind the improvement in heat transfer by drop shape pin fin was increased wetted surface area and delay in thermal flow separation from drop shape pin fin.